ANALISIS PENGARUH NILAI TEKNOLOGI INFORMASI TERHADAP KEUNGGULAN BERSAING PERUSAHAAN (Studi Kasus Pemanfaatan E-Tiketing Terhadap Loyalitas Pengguna Jasa Kereta Api) - Eko Budi Setiawan (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2015)
The main purpose of the implementation of the Information Technology (IT) in a company is to improve the effectiveness of the process, time efficiency and competitive advantage of the company. Use of E-Ticketing is one form of support from companies that can play an important role in improving the competitive advantage in terms of customer loyalty. These results indicate that the quality of information from the E-Ticketing system has no effect on customer satisfaction. The relationship between the variable information quality with satisfaction of -0.087. Quality of E-Ticketing system influence on customer satisfaction with the value of 0.965. The quality of information and the quality of the E-Ticketing system has no effect on customer loyalty with each value of 0.030 and 0.198. While the effect of customer satisfaction on customer loyalty with value of 1.074.